Connoisseurship Consumption Community and Its Dynamics - Quintão, Ronan Torres; Brito, Eliane P. Zamith; Belk, Russell W. (Review of Business Management, 2017)
Purpose – What is the dynamics of the connoisseurship consumption community? What are the forces that drive this serious leisure consumption community? Design/methodology/approach – Adopting a naturalistic inquiry approach, we immersed ourselves in the field, visiting and observing consumers and professionals in independent coffee shops in North America: Toronto, Montreal, Seattle, and New York from August 2013 to July 2014. Findings – The research describes the connoisseurship consumption community and explains its forces, which are education, emulation and tensions between the members of the community. Originality/value – Our findings explain the amateur consumer’s behavior and the relationship of these amateurs with professionals and with the public during their consumption practices. We help to advance the study of heterogeneous consumption communities by revealing the tensions between the members of the community and the production of subcultural and social capital. Our research contributes to the consumer culture field by increasing knowledge of this social consumption phenomenon.